2014
DOI: 10.1111/ejh.12399
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, genetics, and outcome of pediatric patients with hemophagocytic lymphohistiocytosis in Korea: report of a nationwide survey from Korea Histiocytosis Working Party

Abstract: Our study showed the unique predominance of a UNC13D mutation and vulnerability to Epstein-Barr virus infection in Korean children with HLH and emphasizes the prognostic significance of age, liver dysfunction, and treatment responses in this disease. A multicenter prospective trial that builds on the present results is warranted to identify subgroups of patients with a poor prognosis and identify optimal treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 27 publications
4
55
2
1
Order By: Relevance
“…Our study confirmed that HLH is a disorder that mostly affects young children; however, the age of disease onset in this cohort and other Eastern countries is higher than that reported by Western countries . Although primary HLH is predominant in young children, patients younger than 1 year account for only 17% in our cohort, whereas it was 56% in the study reported by the Histiocyte Society .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our study confirmed that HLH is a disorder that mostly affects young children; however, the age of disease onset in this cohort and other Eastern countries is higher than that reported by Western countries . Although primary HLH is predominant in young children, patients younger than 1 year account for only 17% in our cohort, whereas it was 56% in the study reported by the Histiocyte Society .…”
Section: Discussionsupporting
confidence: 85%
“…EBV infection is reported to be a predominant cause of HLH in Asian populations, and accounts for approximately 40% of patients with HLH in Japan and Korea . In our cohort, approximately 75% of patients had a concomitant EBV infection.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…7 Renal involvement, particularly AKI, is seen in up to 50% of patients with HLH. [8][9][10] Clinical manifestations include oliguria, azotemia, and nephrotic syndrome. 9 The spectrum of AKI is similar in patients with secondary HLH.…”
Section: Discussionmentioning
confidence: 99%
“…It accounts for about 40% of all cases of HLH and is the most common type of secondary HLH [13,14]. The diagnosis is es- EBV-HLH in children without underlying disease can be controlled effectively in more than 90% of patients.…”
Section: Acute Ebv-associated Hlhmentioning
confidence: 99%